The views of the elderly on the impact that HIV and AIDS has on their lives in the Thulamela Municipality, Vhembe District, Limpopo province - Vhudivhusi J. Singo; Rachel T. Lebese; Thelma X. Maluleke; Livhuwani H. Nemathaga (AOSIS, 2015)
Background: HIV and AIDS have a devastating impact on the lives of elderly people, particularly so because they are often expected to take care of their terminally ill children and assume the responsibility of looking after children orphaned by AIDS - in most cases with very little resources. Objectives: The study sought to achieve to describe the views of elderly people regarding the impact of HIV and AIDS on their lives, to determine the challenges that elderly people living with HIV or AIDS (EPLWHA) face in their daily lives, and to gain a sense of the coping strategies they use to overcome the obstacles they face in relation to HIV and AIDS. Ethical issues, such as permission to conduct the study, informed consent, confidentiality and anonymity, withdrawal of participation and measure to ensure trustworthiness, were ensured. Design: This was a qualitative, explorative, descriptive study. Participants were interviewedusing an interview guide. Information provided by the participants was captured on a taperecorder and analysed using open coding, and thereafter collated into themes, categories andsub-themes. Results: The study findings revealed that HIV and AIDS have serious negative impacts on the lives of elderly people, particularly those living in poverty. The following key areas in relationto EPLWHA were established: psychological or emotional health, as well as household and socio-economic burdens. Considering the role that elderly people play in the community in so far as HIV and AIDS are concerned, primary health promotion and social welfare programmes should be directed at educating all elderly people and their service providers on how to cope with the health and social problems related to HIV and AIDS.